Publicação Científica Nacional e Internacional sobre Franchising: Levantamento e Análise do Período 1998 - 2007 - Pedro Lucas de Resende Melo; Tales Andreassi (RAC: Revista de Administração Contemporânea, 2010)
The franchising system generates about forty-six billion reais a year in the Brazilian economy by way of 1,197 franchising networks that licnse 65,500 units, generating almost 600,000 direct jobs. In the USA that number is higher still, with around 760,000 units that generate 1.53 trillion dollars a year in the economy. The objective of this paper is to develop an unpublished goal-analysis on franchising involving 61 Brazilian and international scientific papers published from 1998 to 2007 and published by Anpad and in related periodical in Proquest (Qualis A, B or C). Saint approached the following questions: how scientific research into franchises has developed; in which academic vehicles are they linked; the main themes that are dealt with; which institutions these authors are connected with; the participation of states and countries; the predominance of certain authors; the research methods used and the economic segments of application. The results show that Brazilian works are concentrated in Enanpad; the predominance of works on Entrepreneurship and Strategy, internationally, with focus in economic theories; most of the authors are connected to institutions in the south and south-east of Brazil and the USA; a strong predominance of the surveys and the application of the research in several sections of the economy.